Characterization and Comparison of Some Kraft Lignins Isolated from Different Sources - Olgun, Çağrı; Ateş, Saim (MDPI AG, 2023)
Lignin characteristics are significantly affected by kraft processing and isolation conditions. In the studies carried out in this context, commercial lignins or isolated lignins from industrial black solutions are generally preferred. In this study, in order to conduct more comprehensive research, three lignin samples were isolated from kraft black liquor obtained from laboratory cooking trials of pine, poplar, and wheat straw chips, representing softwoods, hardwoods, and annual plants, respectively, according to efficient pulping studies. In addition, another lignin-containing industrial waste was provided from a pulp mill (OBL). The acidification method was applied for isolating lignin from black liquor samples. After isolating the lignin samples from different sources, they were characterized and compared with the commercially available kraft lignin sample (Indulin AT). Total phenolic groups, carboxyl groups, purity, functional groups, nitrobenzene oxidation products, molecular weight, thermal stability, and element contents were analyzed. The isolated lignin samples (except wheat straw) were as pure as commercial lignin. Since the wheat straw was agricultural waste and an annual plant, inorganic elements such as P, K, and Si were more abundant than in the other samples. However, the polydispersity and molecular weight of all of the isolated lignin samples were higher than those of commercial lignin. Because the ash contents of the lignin samples for pine, poplar, OBL, and indulin AT were between 1 and 3%, they can be used for high-value applications. In particular, despite some disadvantages, wheat straw lignin has greater potential for use in extruders than softwood lignins due to their syringyl content.
Keywords: black liquor; kraft lignin; isolating; characterization; comparison; 12. Responsible consumption